Circle home : a novel - Hanlon, Emily (Scarsdale, N.Y. : Bradbury Press, 1981)
A Stone Age girl awakens in the body of twentieth-century girl and must decide whether to return "home" or live as a displaced person in contemporary suburbia.
Keywords: Time travel -- Fiction